El cuento infantil para potenciar el desarrollo del lenguaje oral en los niños de primer grado de educación general básica paralelo “a” de la unidad educativa Dr. Manuel Cabrera Lozano de la ciudad de Loja, período 2017-2018. - Chamba Rueda, Leti Patricia (2018)
The present research is directed to determine how the Children’s Tale helps to enhance the Development of the Oral Language in Children of First Grade of General Basic Education parallel ”A” of Unidad Educativa Dr. Manuel Cabrera Lozano of Loja city, Academic Period 2017-2018. This type of study was descriptive and correlational, the used methods: descriptive, deductive, analytic and statistic: the techniques: surveys to teachers and parents, and the instrument used was the skills oral test which was applied to the children. The study population consisted of 21 children. The obtained information, shows: the 100% of the teachers use the Children’s Tale in the daily work, because it has a great potential to improve the oral language of the children. The skill oral test shows a relevant result with 95% of children that have difficulty in the phonetic part /ll/, after of applying the proposal which consists in a plan of activities for the interval of two months, after that the test is applied again and an improvement is showed with 55% in the correct phoneme articulation /ll/. In conclusion the participation of the children in the storytelling enhance their oral language, the creativity, the social interaction, allowing the values for them. It is recommended to the teachers and parents: take advantage of the storytelling of the Children’s Tale to create the habit of the reading and encourage the values in the children.